Sounding the Alarm: The Code Red Project and Poverty’s Grip on Healthcare - Deng, Florence; Nooristani, Liza; Selvaganesh, Aarani (The Meducator, 2024)
Hamilton is a city of dichotomies. Its dense inner-city and sprawling suburbia constitute a unique microcosm of larger, global wealth inequalities. The entrenchment of poverty has rippling effects on healthcare access and outcomes both within Hamilton and globally, exacerbating discrepancies in the social determinants of health between high-income and low-income populations. Despite having universal healthcare, Canada inadequately addresses healthcare concerns in low-income and homeless populations nationwide and, notably, within Hamilton.